Comparative Analysis of International (Inbound) Tourism Development within Ukraine and Poland - Скутар, Тетяна; Король, Олександр (My University, 2018)
According to UNWTO standards, tourism takes the forms of domestic and international tourism. International tourism is subdivided into inbound and outbound tourism. The statistics of inbound tourism comprises two basic sections: statistics of tourist arrivals and statistics of tourism receipts. The inbound tourism in Poland and Ukraine is researched in this article. It is interesting to analyze the inbound tourism in the neighbouring countries, i.e. Poland and Ukraine, taking into account the “split in time” similarities in the development of the tourism market in these countries, their place in the world tourist flows, as well as attempts of Ukraine to repeat Poland’s experience in its integration into the EU. The aim of this paper is to conduct a comparative analysis of inbound tourist flows in Ukraine and Poland, as well as to reveal the factors influencing tourist arrivals, receipts and profitability as the ratio of the last two. The number and structure of tourist arrivals to Poland and Ukraine in 2000–2016 are analyzed. It was assumed that tourists’ exchange between neighbouring countries probably depends on the length of common land border. To test this assumption, the criterion χ² was used, which is also called the criterion of independence, consistency and homogeneity. The receipts from inbound tourism in above-mentioned countries during the same period of time are estimated. By applying the Consumer Price Index (CPI), the tourism receipts are recalculated for the prices of 2000. The profitability of inbound tourism in Poland and Ukraine in 2013 and 2016 is calculated. The factors influencing tourism receipts and profitability of inbound tourism are described.
Keywords: inbound tourism; international tourism; profitability of inbound tourism; tourism receipts; tourist arrivals